Guidance of Navigating Honeybees by Learned Elongated Ground Structures - Menzel, Randolf; Tison, Lea; Fischer-Nakai, Johannes; Cheeseman, James; Balbuena, Maria Sol; Chen, Xiuxian; Landgraf, Tim; Petrasch, Julian; Polster, Johannes; Greggers, Uwe (Frontiers in Behavioral Neuroscience, 2019)
Elongated landscape features like forest edges, rivers, roads or boundaries of fields are particularly salient landmarks for navigating animals. Here we ask how honeybees learn such structures and how they are used during their homing flights after being released at an unexpected location (catch-and-release paradigm). The experiments were performed in two landscapes that differed with respect to their overall structure: a rather feature-less landscape, and one rich in close and far distant landmarks. We tested three different forms of learning: learning during orientation flights, learning during training to a feeding site, and learning during homing flights after release at an unexpected site within the explored area. We found that bees use elongated ground structures, e.g. a field boundary separating two pastures close to the hive (experiment 1), an irrigation channel (experiment 2), a hedgerow along which the bees were trained (experiment 3), a gravel road close to the hive and the feeder (experiment 4), a path along an irrigation channel with its vegetation close to the feeder (experiment 5) and a gravel road along which bees performed their homing flights (experiment 6). Discrimination and generalization between the learned linear landmarks and similar ones in the test area depend on their object properties (irrigation channel, gravel road, hedgerow) and their compass orientation. We conclude that elongated ground structures are embedded into multiple landscape features indicating that memory of these linear structures is one component of bee navigation. Elongated structures interact and compete with other references. Object identification is an important part of this process. The objects are characterized not only by their appearance but also by their alignment in the compass. Their salience is highest if both components are close to what had been learned. High similarity in appearance can compensate for (partial) compass misalignment, and vice versa.